The sanitary quality of Tifton 85 bermuda grass and Wrangler grass hay stored under different environmental conditions (Bioscience Journal, 2019)
This study evaluated the variations in temperature and dry matter content in Tifton 85 bermudagrass and Wrangler grass hay stored under different environmental conditions. The fungal and mycotoxin populations in the hay production area were also evaluated. Fifty samples (30 hay bales, ten samples of organic matter [OM], and ten samples of grass [G] before baling) were used in a completely randomized design and factorial scheme with ten treatments (a combination of two classes of G: Tifton 85 bermudagrass and Wrangler grass) and three storage systems: a covered shed without side walls, covered with a clear tarp; an open environment covered with a double-sided tarp; and a ventilated closed shed. Four additional treatments, five replications, and one sample per experimental unit completed the study design. The environment influenced the temperature of the Tifton 85 bermudagrass and Wrangler grass bales, and the dry matter content of the bales during the evaluated period was above the recommended limit (800 g kg-1). The genus Penicillium occurred with the highest frequency in the Wrangler grass stored under a double-sided tarp (6.13 log CFU g-1). In the additional treatment, the OM deposited in the soil of the Wrangler grass production area exhibited a greater occurrence of the fungus Fusarium (4.66 log CFU g-1) and of the mycotoxin zearalenone (ZEA; 594.2 μg kg-1). The hay stored in the shed with a clear tarp exhibited more aflatoxin (AFLA) and deoxynivalenol (DON). The concentration of mycotoxins varied across the storage environments and between the stored species; however, the shed storage system used in hay production might also be a source of hay contamination via the incorporation of decomposing OM with mycotoxins in the hay.